A cultura de paz no contexto das Relações Públicas Comunitárias e responsabilidade social - Cabral, Raquel [UNESP]; Gothardo, Josiane [UNESP]; Murback, Lucas [UNESP] (My University, 2014)
In this article we want to approach issues from social responsability and Community Public Relations trough the concept of "Peace Culture", that is still underexplored in this scope. The proposal is to clarify some important aspects of the concept and list them to the nowadays scenary of the organizations that cares about their reputation and image questioning the excellence in social responsability actions linked to a construction of an actually solidary practice in the community.

No presente artigo abordaremos questões de responsabilidade social e Relações Públicas Comunitárias desde a lente da cultura de paz, conceito ainda pouco explorado neste âmbito. A proposta é esclarecer alguns aspectos fundamentais do conceito e relacioná-lo com o cenário atual das organizações, que zelam por sua reputação e imagem, problematizando a excelência em ações de responsabilidade social vinculadas à construção de práticas comunitárias efetivamente solidárias.
Keywords: Peace culture; Social responsability; Community public relations; Organizations; Cultura de paz; Responsabilidade social; Relações Públicas Comunitárias; Organizações